Patristic and text-critical studies : the collected essays of William L. Petersen - Petersen, William Lawrence, 1950-2006. (New Testament Tools, Studies and Documents, 2012)
William L. ("Bill") Petersen (1950-2006) was a prominent Diatessaron scholar and New Testament textual critic. This collection brings together thirty-two of his essays, enabling an overview of his impressive and wide-ranging scholarship on Romanos the Melodist, Tatian and his Diatessaron, Patristic studies, and New Testament textual criticism. It will be of value for all those interested in the state and method of these fields of study, on which it offers engaging and sometimes provocative perspectives.